The role of lncRNA H19 in tumorigenesis and drug resistance of human Cancers - Zhang, Xun; Luo, Mingpeng; Zhang, Jiahang; Guo, Bize; Singh, Shreya; Lin, Xixi; Xiong, Hanchu; Ju, Siwei; Wang, Linbo; Zhou, Yulu; Zhou, Jichun (Frontiers in Genetics, 2022)
Systemic therapy is one of the most significant cancer treatments. However, drug resistance often appears and has become the primary cause of cancer therapy failure. Regulation of drug target, drug metabolism and drug efflux, cell death escape (apoptosis, autophagy, et al.), epigenetic changes, and many other variables are complicatedly involved in the mechanisms of drug resistance. In various types of cancers, long non-coding RNA H19 (lncRNA H19) has been shown to play critical roles in tumor development, proliferation, metastasis, and multiple drug resistance as well. The efficacy of chemotherapy, endocrine therapy, and targeted therapy are all influenced by the expression of H19, especially in breast cancer, liver cancer, lung cancer and colorectal cancer. Here, we summarize the relationship between lncRNA H19 and tumorigenesis, and illustrate the drug resistance mechanisms caused by lncRNA H19 as well. This review may provide more therapeutic potential targets for future cancer treatments.